Oxytrechus gitzeni sp. n. del Peru' (Coleoptera: Carabidae: Trechinae) - Etonti, Mirto (Acta entomologica slovenica (Ljubljana), 2002)
A new species is described, closely related to Oxytrechus paredesi Etonti & Mateu, 1992, from which it differs by morphological characters and the different shape of the aedeagus.
Keywords: Carabidae; Coleoptera; hrošči; Peru